Urinary excretion of indolylacryloylglycine, indolylacetic acid and 5-hydroxyindolylacetic acid in burn patients - Marklová, Eliška; Klein, Leo; Hais, Ivo M (Sborník vědeckých prací lékařské fakulty Univerzity Karlovy v Hradci Králové, 1993)
Indolylacryloylglycine (IAcrGly) is a regular constituent of human urine. Changes in its excretion have been observed, among other conditions, in some skin diseases. Skin lesions in burns are dealt with in the present paper. IAcrGly excretion has been followed during several weeks of hospital treatment and compared with that of two other tryptophan metabolites, namely indolylacetic acid (IAA) and 5-hydroxyindolylacetic acid (5-HIAA). The average excretion of IAcrGly was significantly lower especially between day 3 and 15 post injury. Some alternative explanations of these results are put forward.
Keywords: kyselina hydroxyindoloctová; Humans; Adolescent; lidé; Burns; Hydroxyindoleacetic Acid; Glycine; Female; lidé středního věku; Indoleacetic Acids; Male; mladiství; Adult; kyseliny indoloctové; dospělí; glycin; popálení; Middle Aged; ženské pohlaví; mužské pohlaví